Subsurface characterization and seismic risk mapping in Padang City using HVSR and resistivity data - Octova, Adree; Razi, Pakhrur; Anaperta, Yoszi Mingsi (Journal of Degraded and Mining Lands Management, 2025)
Padang City, situated in a seismically active region, faces significant earthquake risk due to its complex geological structure. This study integrates passive seismic and geoelectrical resistivity methods to characterize subsurface conditions and map seismic vulnerability across 11 districts. Passive seismic data, collected from 84 microtremor stations, were analyzed using the Horizontal-to-Vertical Spectral Ratio (HVSR) method to derive dominant frequency (f?), amplification factor (A?), and seismic vulnerability index (Kg). High Kg values, indicating elevated seismic amplification potential, were observed in Koto Tangah, Kuranji, and parts of South and West Padang. Subsequently, geoelectrical surveys along five targeted lines revealed subsurface heterogeneities, including groundwater-saturated layers and weak sediment zones that heighten liquefaction risk. The integration of HVSR and resistivity data provided a robust framework for identifying high-risk areas with greater precision than single-method approaches. These findings offer critical input for seismic microzonation and urban disaster mitigation planning, underscoring the need for multi-method geophysical assessments in earthquake-prone urban settings.